2008
DOI: 10.1063/1.2969111
|View full text |Cite
|
Sign up to set email alerts
|

The geometric, optical, and magnetic properties of the endohedral stannaspherenes M@Sn12 (M=Ti, V, Cr, Mn, Fe, Co, Ni)

Abstract: The geometric, optical, and magnetic properties of the M@Sn(12) clusters (M=Ti, V, Cr, Mn, Fe, Co, Ni) are studied using the relativistic density-functional method. The geometric optimization shows that the ground states of these clusters are probably very close to the I(h) structure. Our calculations demonstrate that the optical gaps of the M@Sn(12) can be tuned from infrared to green, and the magnetic moments of them vary from 2 mu(B) to 5 mu(B) by doping d transition metal atoms into Sn(12) cage, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…LU-MO + 2, indicating that the 3d electrons play an very important role in the electronic excitation spectrum. This character further approves the conclusion that the hybridization between 3d of M and 3s, 3p states of Si in MSi 12 clusters is stronger than that between 3d of M and 5s, 5p of Sn in MSn 12 clusters (M = Ti-Ni), which has been confirmed by their magnetic property [7,47]. Moreover, even for the M with filled 3d shell (Cu and Zn), the participation of 3d orbitals in electronic excitation is still impressive.…”
Section: Optical Absorption Spectrasupporting
confidence: 82%
“…LU-MO + 2, indicating that the 3d electrons play an very important role in the electronic excitation spectrum. This character further approves the conclusion that the hybridization between 3d of M and 3s, 3p states of Si in MSi 12 clusters is stronger than that between 3d of M and 5s, 5p of Sn in MSn 12 clusters (M = Ti-Ni), which has been confirmed by their magnetic property [7,47]. Moreover, even for the M with filled 3d shell (Cu and Zn), the participation of 3d orbitals in electronic excitation is still impressive.…”
Section: Optical Absorption Spectrasupporting
confidence: 82%
“…During the last few decades, copper clusters have been demonstrated to have similar catalytic activities with those of gold clusters for the low temperature CO oxidation and partial oxidation of hydrocarbons 1 2 3 4 5 6 . At the same time, theoretical and experimental work has also shown that the nature of small clusters can be considerably modified by the addition of impurity atom(s) 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 . Copper clusters doped with different transition-metal atoms have been expected to tailor the desired catalytic, electronic, magnetic and optical properties for potential applications in solid state chemistry, microelectronics, nanotechnology and materials science 40 41 42 43 44 45 46 47 48 49 50 .…”
mentioning
confidence: 99%
“…It can trap an atom from most of the transition metals or f‐block elements to form endohedral stannaspherenes, which possess diverse magnetic and optical properties . While previous studies only focus on isolated stannaspherene clusters or cluster dimers, their possibility of forming extended ferromagnetic materials remains to be explored.…”
Section: Background and Originality Contentmentioning
confidence: 99%